A quantitative PCR approach to determine gene copy number - Peter S. Solomon; Simon V.S. Ipcho; James K. Hane; Kar-Chun Tan; Richard P. Oliver (Fungal Genetics Reports, 2008)
Here, we report on the use of quantitative PCR (qPCR) to determine gene copy number in filamentous fungi. Using the sequenced dothideomycete Stagonospora nodorum, qPCR was used to unequivocally confirm the presence of single, two and three copy regions as predicted by in silico PCR. Further validation of the technique was demonstrated by verifying the copy numbers of introduced gene cassettes in previously characterised transformants of S. nodorum. Apart from increased sensitivity, this technique offers a high-throughput alternative to Southern blots for determining gene copy number, a significant factor when screening fungal mutants and transformants.